Administration of Paracetamol, Diclofenac Sodium, and Tramadol for Postoperative Analgesia After_x000D_ Coronary Artery Bypass Surgery - (:unkn) unknown (My University, 2018)
Objective: In this study we aimed to compare the effects of paracetamol, diclofenac sodium, and tramadol administration on postoperative pain during postoperative period of the patients who underwent coronary artery bypass grafting (CABG).Material and Method: After acquirement of the approval of ethics committee and informed consent of the patients, 200 patients with normal renal and liver functions and an ejection fraction value of 40 % who would undergo CABG were included in the study. The patients were randomly divided into four groups: Group I (n=50) paracetamol group (IV); Group II (n=50) diclofenac sodium (IM) group; Group III (n=50) tramadol (IV) group, and Group IV (n=50) placebo group. Group IV patients were given only 2 μg/kg/h of fentanyl. Hemodynamic values and biochemical parameters were recorded. Postoperative pain was assessed using Visual Analog Scale (VAS).Results: In the placebo group, PaCO2 levels were higher, mean arterial pressure was higher and extubation time was longer than the other groups. There was no statistically significant difference between the three analgesia groups.Conclusion: Based on our study results, analgesic effect of IV paracetamol appears to be similar to diclofenac and tramadol.

Amaç: Bu çalışmada, koroner arter baypas (KABG) ameliyatı geçiren hastalara postoperatif süreçte parasetamol, diklofenak sodyum ve tramadol uygulamasının postoperatif ağrı üzerine etkilerini karşılaştırmayı amaçladık._x000D_ Gereç ve Yöntem: Etik komite ve bilgilendirilmiş onamları alınan KABG uygulanacak normal böbrek ve karaciğer fonksiyonlarına sahip ve ejeksiyon fraksiyonu %40 üzerinde olan 200 hasta çalışmaya alındı. Hastalar rastgele 4 gruba ayrıldı; grup I (n=50) parasetamol IV, grup II (n=50) diklofenak sodyum IM, group III (n=50) IV tramadol alan hastalar, ve grup IV (n=50) plasebo. Grup IV’teki hastalar yalnızca 2 μg/kg/saat fentanil aldı. Hemodinamik ve biyokimyasal parametreler kaydedildi. Postoperatif ağrı vizüel analog skala (VAS) ile değerlendirildi._x000D_ Bulgular: Plasebo grubunda ekstübasyon zamanı daha uzun, PaCO2 seviyeleri ve ortalama kan basıncı diğer gruplara göre daha yüksekti. Diğer analjezi grupları arasında istatistiksel olarak anlamlı fark yoktu._x000D_ Sonuç: Çalışmamızda, IV parasetamolün analjezik etkisinin diklofenak ve tramadole benzer olduğu görüldü.
Koroner Arter Baypas Cerrahisinden Sonra Postoperatif Analjezide Parasetamol, Diklofenak Sodyum ve Tramadol Verilmesi